Evaluasi Pemilihan Sustainable Supplier Dolomit Dengan Metode FAHP dan TOPSIS Di PT. Petrokimia Gresik - Nuswantoro, Wira Yudha; Ernawati, Dira; Nugraha, Isna (BRILIANT: Jurnal Riset dan Konseptual, 2025)
PT. Petrokimia Gresik, the most comprehensive fertilizer agro-industry company in Indonesia, produces a product called Filler Plus, which requires dolomite as a raw material. Amid pressure from the government, especially on environmental issues, companies are creating production strategies that are environmentally friendly but also prioritize economic factors (economic profits) and the impact on the social environment. One of these strategies can be done by selecting the right supplier. This research evaluates supplier performance based on sustainable aspects (economic, environmental, social) using the cut-off point method for selecting sub-criteria, FAHP for weighting sub-criteria, and TOPSIS for ranking suppliers based on predetermined sub-criteria. This study uses qualitative and quantitative approaches. The research results show that supplier S2 is ranked highest with a coefficient value of 0.826, followed by S3 (0.442), S4 (0.357), and S1 (0.256). This study can serve as a basis for strategic decision-making in selecting sustainable dolomite suppliers by considering the most relevant criteria and sub-criteria.